Den patriarkalske Abraham - Jensen, Hans Jørgen Lundager (Dansk Teologisk Tidsskrift, 2015)
Behind the well-known “theological” Abraham in Genesis lies the narrative figure that invites an analysis inspired by sociology and anthropology. Abraham is pictured as a wealthy slave- and cattle-owner, competent in negotiation and trade. In matters concerning economy and kinship Abraham is the moderate mediator between violent extremes. In Mary Douglas’ Grid/Group scheme, Abraham would be equally remote from priestly-hierarchical and deuteronomistic-enclavist ideals. Underneath the pietistic and ethnocentric themes that the Biblical textual process has added to the figure of Abraham, one can still detect a third position, an alternative to temple-ritualism and to religious zealotry.